Quantitative proteome profiling of lymph node-positive vs. -negative colorectal carcinomas pinpoints MX1 as a marker for lymph node metastasis - Croner, Roland S.; Stürzl, Michael; Rau, Tilman; Metodieva, Gergana; Geppert, Carol-Immanuel; Naschberger, Elisabeth; Lausen, Berthold; Metodiev, Metodi V. (International Journal of Cancer, 2014)
We used high-resolution mass spectrometry to measure the abundance of more than 9,000 proteins in 19 individually dissected colorectal tumors representing lymph node metastatic (n = 10) and nonmetastatic (n = 9) phenotypes. Statistical analysis identified MX1 and several other proteins as overexpressed in lymph node-positive tumors. MX1, IGF1-R and IRF2BP1 showed significantly different expression in immunohistochemical validation (Wilcoxon test p = 0.007 for IGF1-R, p = 0.04 for IRF2BP1 and p = 0.02 for MX1 at the invasion front) in the validation cohort. Knockout of MX1 by siRNA in cell cultures and wound healing assays provided additional evidence for the involvement of this protein in tumor invasion. The collection of identified and quantified proteins to our knowledge is the largest tumor proteome dataset available at the present. The identified proteins can give insights into the mechanisms of lymphatic metastasis in colorectal carcinoma and may act as prognostic markers and therapeutic targets after further prospective validation.
EVALuna2:6585